2010
DOI: 10.1002/j.2168-9830.2010.tb01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of 3D Simulation Based Learning on the Motivation and Performance of Engineering Students

Abstract: BACKGROUNDSimulation-based Learning (SBL) was used in Machining Technology, a sixtyhour module for second year engineering students, at the School of Engineering at Temasek Polytechnic. The aim of this study was to investigate the effect of SBL on learners' motivation and performance. In assessing students' motivation, we adopted a framework based on the Self-determination Theory (SDT), chosen on account of its comprehensive treatment of the relationship between students' perceived needs satisfaction and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 64 publications
(47 reference statements)
7
87
1
Order By: Relevance
“…The need for autonomy was fulfilled by giving students independence during the project; the need for competence was realized by guidance and focused definition of the sub-tasks throughout the project; and finally, the need for relatedness was satisfied due to the personal attitude provided by the teaching staff. These results conform to the recent findings of Koh et al [16] who showed that a course that provided the three above mentioned needs improved intrinsic motivation among mechanical engineering students.…”
Section: Discussion and Summarysupporting
confidence: 92%
“…The need for autonomy was fulfilled by giving students independence during the project; the need for competence was realized by guidance and focused definition of the sub-tasks throughout the project; and finally, the need for relatedness was satisfied due to the personal attitude provided by the teaching staff. These results conform to the recent findings of Koh et al [16] who showed that a course that provided the three above mentioned needs improved intrinsic motivation among mechanical engineering students.…”
Section: Discussion and Summarysupporting
confidence: 92%
“…The abovementioned results conform to the findings by [25][26] that show an improvement in the intrinsic motivation of engineering students who attended courses that have fulfilled these three needs. It is especially interesting to compare the results with those received at a study examining the motivation of engineering students who had demonstrated laboratory experiments at high schools in Brazil [6].…”
Section: Need Example Interpretationsupporting
confidence: 89%
“…For instance, Koh et al [25] showed that simulation based learning among mechanical engineering students has provided the three needs discussed, and thus improved the intrinsic motivation. Additionally, Gero [26] found a significant improvement in the intrinsic motivation of electrical engineering students who took an introductory course that has fulfilled these needs.…”
Section: Paper Engineering Students As Science Teachers: a Case Studymentioning
confidence: 99%
“…First, simulations can improve students' motivation to learn by delivering information to students in a way that heightens their interest in understanding it. Through prompt feedback, challenging but achievable goals, uncertain outcomes, and the generation of feelings of autonomy, accomplishment, relevance, relatedness to others, and pleasure among participants, simulations can enhance students' extrinsic and intrinsic motivation (Carnes 2011;Koh et al 2010;Mitchell and Savill-Smith 2004). According to de Freitas (2006:350), " [o]ne of the main perceived advantages of using games and simulations [is] increased motivational levels for learners."…”
Section: Simulationsmentioning
confidence: 99%